Educational content related to postcolonialism and indigenous health inequities recommended for all rehabilitation students in Canada: a qualitative study. Issue 26 (18th December 2018) - Hojjati, Ala; Beavis, Allana S. W.; Kassam, Aly; Choudhury, Daniel; Fraser, Michelle; Masching, Renée; Nixon, Stephanie A.
Abstract: Background: Postcolonial analysis can help rehabilitation providers understand how colonization and racialization create and sustain health inequities faced by indigenous peoples. However, there is little guidance in the literature regarding inclusion of postcolonialism within rehabilitation educational curricula. Therefore, this study explored perspectives regarding educational content related to postcolonialism and indigenous health that rehabilitation students in Canada should learn to increase health equity. Methods: This qualitative study involved in-depth, semi-structured interviews with 19 individuals with insight into postcolonialism and health in Canada. Data were analyzed collaboratively to identify, code, and translate themes according to a structured six-phase method. Results: Four themes emerged regarding educational content for rehabilitation students: (1) the historic trauma of colonization and its ongoing impacts on rehabilitation for indigenous peoples; (2) disproportionate health burden and inequitable access to health services; (3) how rehabilitation is related to Indigenous ways of knowing; and (4) why rehabilitation is well-positioned to address health inequities with Indigenous Peoples. Conclusion: Results call for reflection on assumptions underpinning the rehabilitation professions that may unintentionally reinforce health inequities. A postcolonial lens can help rehabilitation educators promote culturally safe services for people whose ill health and disability are linked to the effects of colonization. Implications for Rehabilitation: Given the powerful, ongoing effects of colonization and racialization on health and disability, recommendation #24 from the Truth and Reconciliation Commission of Canada calls for the education of health professionals related to Indigenous history, rights, and anti-racism. However, there is little curricula on these areas in the education of rehabilitation professional students or in continuing education programs for practicing clinicians. This is the first study to investigate expert perspectives on content related to postcolonialism and indigenous-settler inequities that should be included in the education of rehabilitation students in Canada. According to the participants in this study, rehabilitation educators in Canada should consider incorporating the following four themes into curricula to better address Indigenous-settler inequities in the context of rehabilitation: (1) the historic trauma of colonization and its ongoing impacts on rehabilitation for Indigenous Peoples in Canada; (2) disproportionate health burden and inequitable access to health services; (3) how rehabilitation is related to Indigenous ways of knowing; and (4) why rehabilitation is well-positioned to rise to the challenge of addressing health inequities with Indigenous Peoples in Canada. Postcolonialism is useful for rehabilitation providers because it is an approach that redirects the focus of problems from Indigenous People to the systems of oppression (specifically colonization and racialization) that cause ill health and disability.